Anomalous origin of the right coronary artery with interarterial course, an incidental finding in a pediatric patient with Kawasaki disease: report of a case - Baena Gómez, Jessica P.; Sáenz López, José D.; Vergara Vergara, Gabriel (Revista del Hospital Italiano de Buenos Aires, 2026)
Congenital anomalies of the coronary arteries are uncommon and mostly involve abnormalities in the origin and course of the coronary vessels. We present the case of an 8-year-old pediatric patient with prolonged febrile syndrome and mucocutaneous manifestations, in whom incomplete Kawasaki disease was clinically suspected. During the diagnostic workup and imaging evaluation, an anomalous origin of the right coronary artery from the left coronary sinus, with an interarterial course and significant proximal narrowing, was incidentally identified. The imaging findings, their anatomical relevance, and the associated clinical risks are described, highlighting the educational value of coronary CT angiography in accurately characterizing coronary anatomy and differentiating congenital anomalies from potential acquired dilatations in the context of systemic inflammatory disease.